(untitled) (Journal of University of Babylon for Engineering Sciences, 2018)
An experimental investigation is carried out on the use of water injection on the humidification process of air with a steady flow that travels during the curved part of a duct with a constant cross section. The naturally generated turbulences will surely aid the mixing process between the injected water droplets and the air to enhance both the mass and heat transfer. The current investigation is regarded as a simulation of the inlet air cooling of the gas turbine which aims to specify the optimum atomizer position on the air cooling by the fogging technique. The experiments were carried out on a (50×50 cm) wind tunnel with an average air velocity of (10 m/s). Experiments were conducted in a range of air to water flow ratio between 1000 and 2000, and an ambient temperature in a range of 30° to 50°C. At higher ambient temperature of 45.2oC (DBT), a temperature reduction of 26% and an increase in the relative humidity ratio of 2.13 were recorded at the flow ratio of 1000. Injecting water upward through the range of angles -25° to 75° showed less sensitivity to atomizer location regardless the radial position of the atomizer. This situation is most suitable for using atomizing array across the duct. The central location with tangential spray introduces the critical position for a single-point spray. Such position is promising the optimum atomizer place specified by a radii ratio of (r/rin=3) and tangential orientation to the direction of flow.